The impact of workplace ergonomics and neck-specific exercise versus ergonomics and health promotion interventions on office worker productivity: A cluster-randomized trial - Pereira, Michelle; Comans, Tracy; Sjøgaard, Gisela; Straker, Leon; Melloh, Markus; O’Leary, Shaun; Chen, Xiaoqi; Johnston, Venerina (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVES ': 'Using an employer’s perspective, this study aimed to compare the immediate and longer-term impact of workplace ergonomics and neck-specific exercise versus ergonomics and health promotion information on health-related productivity among a general population of office workers and those with neck pain. ' ' METHODS ': 'A prospective one-year cluster randomized trial was conducted. Participants received an individualized workstation ergonomics intervention, combined with 12 weeks of either workplace neck-specific exercises or health promotion information. Health-related productivity at baseline, post-intervention and 12-months was measured with the Health and Work Performance Questionnaire. Intention-to-treat analysis was performed using multilevel mixed models. ' ' RESULTS ': 'We recruited 763 office workers from 14 organizations and allocated them to 100 clusters. For the general population of office workers, monetized productivity loss at 12 months [AU1464 (standard deviation [SD] 1318) versus AU1563 (SD=1039); P=0.023]; and presenteeism at 12 months [2.0 (SD 1.2) versus 2.4 (SD 1.4); P=0.007] was lower in the exercise group compared to those in the health promotion information group. For office workers with neck pain, exercise participants had lower sickness absenteeism at 12 months compared to health promotion information participants [0.7 days (SD 1.0) versus 1.4 days (SD 3.1); P-=0.012], despite a short-term increase in sickness absenteeism post-intervention compared to baseline for the exercise group [1.2 days (SD 2.2) versus 0.6 days (SD 0.9); P<0.001]. ' ' CONCLUSION ': 'A workplace intervention combining ergonomics and neck-specific exercise offers possible benefits for sickness presenteeism and health-related productivity loss among a general population of office workers and sickness absenteeism for office workers with neck pain in the longer-term.
Keywords: absenteeism; cluster-randomized trial; efficiency; ergonomics; health promotion; health promotion intervention; intervention; musculoskeletal disease; neck; neck pain; neck-specific exercise; occupational health; office worker; productivity; workplace